You are trying to put it into slope intercept form, which is: y = mx + b
3) (-4, -2), slope = 3/4
Note that -4 = x, -2 = y, 3/4 = m
-2 = (3/4)(-2) + b
Simplify
-2 = -6/4 + b
b = 6/4 - 2
b = -2/4, or -1/2
y = 3/4x - 1/2 is your slope intercept form
-----------------------------------------------------------------------------------------------------------------
Again, the slope intercept form is: y = mx + b
Plug in
10 = -6(-1) + b
Simplify
10 = 6 + b
Isolate the b. Subtract 6 from both sides
10 (-6) = 6 (-6) + b
b = 10 - 6
b = 4
Slope intercept form: y = -6x + 4
-----------------------------------------------------------------------------------------------------------------
hope this helps